Crisis management during anaesthesia: hypertension. Issue 3 (2nd June 2005) - Paix, A D; Runciman, W B; Horan, B F; Chapman, M J; Currie, M
Abstract : Background: Hypertension occurs commonly during anaesthesia and is usually promptly and appropriately treated by anaesthetists. However, its recognition is dependent on correctly functioning and calibrated monitors. If it is not diagnosed and/or promptly corrected, it has the potential to cause significant morbidity and even mortality. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK" supplemented by a specific sub-algorithm for the management of hypertension occurring in association with anaesthesia. Methods: The potential performance of this approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: There were 70 reports of intraoperative hypertension among the first 4000 incidents reported to AIMS. Drug related causes accounted for 59% of all incidents. It was considered that, properly applied, this structured approach would have led to a quicker and/or better resolution of the problem in 21% of the cases. Conclusion: Once hypertension is identified and confirmed, its rapid control by the careful use of a volatile anaesthetic agent, intravenous opioids, or rapidly acting antihypertensives will usually avoid serious morbidity. If hypertension is unresponsive to the treatment recommended in the relevant sub-algorithm, an unusual cause such as phaeochromocytoma, carcinoid syndrome, or thyroid storm should be considered.